If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 + 8x = 7(x + 6) Reorder the terms: 39 + 8x = 7(6 + x) 39 + 8x = (6 * 7 + x * 7) 39 + 8x = (42 + 7x) Solving 39 + 8x = 42 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 39 + 8x + -7x = 42 + 7x + -7x Combine like terms: 8x + -7x = 1x 39 + 1x = 42 + 7x + -7x Combine like terms: 7x + -7x = 0 39 + 1x = 42 + 0 39 + 1x = 42 Add '-39' to each side of the equation. 39 + -39 + 1x = 42 + -39 Combine like terms: 39 + -39 = 0 0 + 1x = 42 + -39 1x = 42 + -39 Combine like terms: 42 + -39 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 6n-13=12-4n | | 42=(x-2)-7 | | 12a+24=72 | | 3n+1=7-n | | 16-6h=9(5h-3) | | 24x^2+32x-6= | | 220f*178g=g | | 10(11u+6) = 14u+2 | | 52y=-26-26x | | X=-3siny | | 3x-6+2x=13 | | 16=4n-6n | | 15-2n=20-3n | | 6x-5x+48x-40= | | (2x-30)=(x-15) | | y=20(1.2)^80/30 | | 8-n=15-2n | | 4k+7k=-15 | | 9i+7=5i | | 2x-30=x-15 | | (3/7)=10p-(1/7) | | (ln(x))^(-1/3) | | 2n-5=15-3n | | 3a+2b=3(4)+2(9) | | 0.8=2.3333333333333333333333333x | | 15-3n=4n-6 | | 6v-4+2(3v+6)=-2(v+4) | | v(11v+3)-8=0 | | 29=-7+4(z+9) | | m=5(2-1) | | 2x-1=4x-6 | | 5x-7=2[1+x] |